2017
DOI: 10.1002/ep.12742
|View full text |Cite
|
Sign up to set email alerts
|

Solvent free acetalization of glycerol with formaldehyde over hierarchical zeolite of BEA topology

Abstract: The hierarchical H/BEA zeolites were prepared by postsynthesis treatment. The portion of the parent H/BEA zeolite was treated with aqueous 0.1 M NaOH solution with different alkali volume to H/BEA zeolite weight (5, 10, 30,150, and 300 mL/g) ratios. The physicochemical properties of samples were evaluated by powder X‐ray diffraction, Pyridine Fourier transform infrared spectroscopy, NH3 temperature programme desorption, Nitrogen adsorption/desorption isotherms, and magic angle spinning nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…While, in the reaction between glycerol with formaldehyde, the produced hemiacetal formation is not a stable carbenium ion. Thus, the conversion value for the glycerol-formaldehyde system is relatively small as compared to the reaction where acetone is used as a co-reactant [57][58][59]. between glycerol with formaldehyde, the produced hemiacetal formation is not a stable carbenium ion.…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 99%
“…While, in the reaction between glycerol with formaldehyde, the produced hemiacetal formation is not a stable carbenium ion. Thus, the conversion value for the glycerol-formaldehyde system is relatively small as compared to the reaction where acetone is used as a co-reactant [57][58][59]. between glycerol with formaldehyde, the produced hemiacetal formation is not a stable carbenium ion.…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 99%
“…The poor catalytic activity of the ZSM-5 and Y zeolites can be explained in terms of the narrow pore structure and the hydrophilic character respectively. Dealuminated and desilicated Hbeta zeolites were prepared and applied to the acetalization of glycerol by Venkatesha et al [ 33 ] and Bokade et al [ 34 ], respectively. Both groups concluded that the enhanced catalytic performances were due to the increased pore volumes by dealumination or silication.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal value of the concentration of NaOH was found to be 0.2M and the optimal time for the treatment was found to be 120 secs. [14][15][16] Higher concentrations of NaOH was found to weaken the crystalline structure of the zeolite. In some of the works, after the desilication process ion exchanging with ammonium nitrate solution was done to get back the protonic form of the hierarchical zeolite.…”
Section: Desilicationmentioning
confidence: 99%
“…Desilication is a well-known post synthesis treatment and it is one of the simplest routes to hierarchical zeolites. [14][15][16][17][18][19][20][21][22][23] Desilication is done under alkaline conditions and the usual procedure is treating with sodium hydroxide(NaOH). The optimal value of the concentration of NaOH was found to be 0.2M and the optimal time for the treatment was found to be 120 secs.…”
Section: Desilicationmentioning
confidence: 99%
See 1 more Smart Citation